Recent Advances on Renewable and Biodegradable Cellulose Nanopaper Substrates for Transparent Light-Harvesting Devices: Interaction with Humid Environment - Alessandra Operamolla (International Journal of Photoenergy)
Cellulose nanopaper (CNP) has attracted much interest during the last decade as a new fascinating renewable and biodegradable substrate for printed electronics and solar cells. Its outstanding optical and mechanical properties make CNP the ideal substrate for the preparation of photovoltaic devices, since its high transparency and haze favour the absorption of light from the active layer of the solar cell. However, some advances need to be done in the direction of increasing CNP stability in humid environment without compromising its remarkable advantages. This review critically points at these aspects, presenting an overview of state-of-art solutions to enhance nanopaper stability in a humid environment.